2022
DOI: 10.22146/ijc.72774
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of a tRNA-Leucine Dimer with an A3243G Heteroplasmy Mutation in Human Mitochondria Using a Secondary Structure Prediction Approach

Abstract: Mitochondrial DNA mutations, such as A3243G, can affect changes in the structure of biomolecules, resulting in changes in the structure of Leucine transfer Ribose Nucleic Acid to form a dimer. Dimer structure modeling is needed to determine the properties of the structure. However, the lack of a structure template for the transfer of Ribose Nucleic Acid (tRNA) is challenging for the modeling of mutant structures of tRNA, especially mitochondrial tRNA that are susceptible to mutation. Therefore, this study pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…T10609C and C10676G mutations in mitochondrial DNA can affect proton translocation, leading to MELAS (mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes), ataxia, CPEO (chronic progressive external ophthalmoplegia), LHON (Leber hereditary optic neuropathy), and MIDD (maternally inherited diabetes and deficiency) [ 32 ]. This mutation is often accompanied by mutations in A3243G and G9053A, which can alter the structure of the mitochondrial leucine tRNA and ATPase6 [ 33 , 34 ] and trigger an increase in cellular oxidative stress. Therefore, mangostin compounds have the potential to become mitochondrial antidiabetic compounds that can be used in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…T10609C and C10676G mutations in mitochondrial DNA can affect proton translocation, leading to MELAS (mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes), ataxia, CPEO (chronic progressive external ophthalmoplegia), LHON (Leber hereditary optic neuropathy), and MIDD (maternally inherited diabetes and deficiency) [ 32 ]. This mutation is often accompanied by mutations in A3243G and G9053A, which can alter the structure of the mitochondrial leucine tRNA and ATPase6 [ 33 , 34 ] and trigger an increase in cellular oxidative stress. Therefore, mangostin compounds have the potential to become mitochondrial antidiabetic compounds that can be used in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…The results predicted stability in terms of binding energy and root mean square deviation (RMSD). The results show that the RMSD value of the dimer structure of the mutant leucine tRNA is lower because there are more hydrogen bonds than there are on a normal dimer [ 93 ]. Recent research has proved in silico the effect of the mitochondrial DNA tRNA leucine A3243G mutation in patients with type 2 DM.…”
Section: Aptasensor For Diagnosis Of Diabetes Mellitus and Mitochondr...mentioning
confidence: 99%
“…In addition, molecular dynamics simulations on the dimeric tRNA Leu with the A3243G heteroplasmy mutation in human mitochondria showed that the structure of the mutant tRNA Leu dimer is more stable than the wildtype tRNA dimer based on the conformational energy and RMSD value. The value of mutant tRNA Leu dimers is lower than the wildtype tRNA Leu dimers as evidenced by the presence of more intermolecular hydrogen bonds [ 112 ]. Enzymes that assist aminoacylation will experience a decrease in their activity against dimeric substrates, causing the tRNA to become “uncharged” which means it does not carry amino acids so that it impacts the mitochondrial subunit protein which requires the amino acid leucine during translation.…”
Section: Association Between Transfer Rna Mutations and Type 2 Diabet...mentioning
confidence: 99%